Hair dye allergies: available alternatives - Gurusamy, Sukanya; Danny, Celestin Geo; S., Gayathri; Sundarara, Divyabharathi (International Journal of Research in Dermatology, 2024)
P-phenylenediamine (PPD) is a well-known sensitizer of skin which forms a major component in permanent hair dyes. Allergic contact dermatitis induced by PPD is a major concern for hairdye industry and the population using hair dyes. To reduce the burden of contact dermatitis due to PPD in hair dyes, various alternative hair dye molecules have been developed over the years which include two-methoxymethyl-p-phenylenediamine (ME-PPD) molecule and hydroxyethyl-p-phenylenediamine (HE PPD) molecule. These both molecules have shown reduced sensitization to skin and much lower skin permeability which makes them as safer alternatives to PPD hair dyes in the market.